Core competencies, matching, and the structure of foreign direct investment - Federico J. Díez; Alan C. Spearot (Federal Reserve Bank of Boston, 2011)
We develop a matching model of foreign direct investment to study how multinational firms choose between greenfield investment, acquisitions, and joint ventures. For all entry modes, firms must invest in a continuum of tasks to bring a product to market. Each firm possesses a core competency in the task space, though firms are otherwise identical. For acquisitions and joint ventures, a multinational enterprise (MNE) must match with a local partner, where the local partner may provide complementary expertise within the task space. However, for joint ventures, investment in tasks is shared by multiple owners, and hence is subject to a holdup problem. In equilibrium, ex-ante identical multinational enter the local matching market, and ex post, three different types of ownership within a heterogeneous group of firms arise. Specifically, the worst matches dissolve and the MNEs invest greenfield, the middle matches form joint ventures, and the best matches integrate via mergers and acquisitions. We also show that joint ventures are more common when the host country produces products that are inferior to those produced in the source country, which explains why MNEs use joint ventures more frequently in less-developed countries. Finally, we extend the model to a simple two-period context to provide a rationale for one of the more salient features of joint ventures, namely, their instability.
Keywords: F12; F23; 330